2017
DOI: 10.1016/j.cirp.2017.04.124
|View full text |Cite
|
Sign up to set email alerts
|

Direct electroplating of plastic for advanced electrical applications

Abstract: Electrodeposition or electroplating is predominantly applied to metallic components. Electroplating of plastics is possible in some cases where an initial electroless plating layer of nickel or copper is made to provide a conductive surface on the plastic part. This paper proposes a method for direct electroplating of plastic eliminating the need for slow and expensive processes like electroless metal deposition, PVD coating, painting with conductive inks etc. The results obtained from the test demonstrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The used set-up is the modified version of the set-up depicted in our previous publication. 20 In order to ensure the effective contact between the electrodes and the specimen surfaces, the contacting areas were sanded. Conductive carbon tapes were also placed between the contacts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The used set-up is the modified version of the set-up depicted in our previous publication. 20 In order to ensure the effective contact between the electrodes and the specimen surfaces, the contacting areas were sanded. Conductive carbon tapes were also placed between the contacts.…”
Section: Methodsmentioning
confidence: 99%
“…Electrical resistivity of the inner part was measured using two copper electrodes contacting the two ends of the test specimen under constant pressure using the relevant range ohmmeter (Hioki, Japan). The used set-up is the modified version of the setup depicted in our previous publication 20 . In order to ensure the effective contact between the electrodes and the specimen surfaces, the contacting areas were sanded.…”
Section: Characterizationmentioning
confidence: 99%
“…Nowadays, Cu can be even electrodeposited on plastics and polymers given the development of conductive polymers and doped plastics. This possibility made Cu a suitable target for electronics, microelectronics, solar cells, transistors, and IT gadgets (cellular phones or chips) as flexible interconnections that are known as flexible circuit boards (FCBs) [18][19][20][21][22]. However, the poor corrosion and oxidation resistance of Cu alloys, especially in the presence of aggressive ions like chlorides, is their biggest disadvantage.…”
Section: Introductionmentioning
confidence: 99%
“…Creating separate electrodes using electroless plating requires additional steps to define the conductors, for instance through laser ablation, [13] variable swelling, [14] or mechanical polishing. [16] Based on this finding, we demonstrated selective electroplating of a 3D printed fused filament fabrication (FFF) part, combining conductive composite filament to define plated regions with a nonconductive plastic as a mechanical support. [16] Based on this finding, we demonstrated selective electroplating of a 3D printed fused filament fabrication (FFF) part, combining conductive composite filament to define plated regions with a nonconductive plastic as a mechanical support.…”
mentioning
confidence: 99%
“…[15] In 2017, researchers demonstrated that conductive polymer composites can be used as a conductive seed layer for electroplating. [16] Based on this finding, we demonstrated selective electroplating of a 3D printed fused filament fabrication (FFF) part, combining conductive composite filament to define plated regions with a nonconductive plastic as a mechanical support. [17] Fused filament fabrication, the extrusion of melted thermoplastics to build a part, is a cheap and widely available 3D printing technology.…”
mentioning
confidence: 99%